TV captures terrorism on September 11 : an augmented reading experience - Berne, Emma Carlson (Captured television history., 2019)
Examines how the terrorist attacks of September 11, 2001, were covered on live television, discussing the lack of commercial breaks, reporting from the street and the news studio, and the ways coverage changed. Includes critical thinking questions, a timeline, color photographs, a glossary, an accompanying app, and further resources.